STRUKTUR POPULASI DAN SEJARAH KOLONISASI IKAN BOTIA (Chromobotia macracanthus BLEEKER) ASAL SUMATERA DAN KALIMANTAN BERDASARKAN SEKUEN INTRON DARI GEN ALDOLASE-B - Sudarto Sudarto; Laurent Pouyaud; Ruby V. Kusuma (Universitas Gadjah Mada, 2008)
Clown loach (Chromobotia macracanthus Bleeker) or botia is an endemic species of Indonesia belonging to Cobitidae family which has restricted distribution only in Sumatra in Pangabuang, Kwanten, Batanghari, Teluk Betung, Musi riverines, and in Kalimantan found in Barito, Kahayan, Kapuas, Bongan dan Mahakam rivers. The objectives of this study are to find the genetical population structure and the history of colonization of clown loach from Kalimantan (Kapuas river) dan Sumatra (Batanghari, Musi and Tulang Bawang rivers) based on intron sequence of Aldolase B gene. Cutting fins are collected from each location and preserved in ethanol solution and stored in deep freezer before digested for DNA analysis by proteinase-K method followed by CTAB (cethyl/hexadecyl trimethyl ammonium bromide) method; then amplified by EPIC-PCR (Exon Primed Intron Crossing Polymerase Chain Reaction) techniques. PCR product were Electrophoreted and DNA bands were sequenced. The results of sequences analysis showed 8 types of alleles, 5 types for type A alleles (A-1, A-2, A-3, A-4, A-5), 2 type B alleles (B-1 and B-2) and C-1. There was a genetic difference between Sumatra and Kalimantan populations.